Local control and patient reported outcomes after online MR guided stereotactic body radiotherapy of liver metastases - Uder, Laura; Nachbar, Marcel; Butzer, Sarah; Boldt, Jessica; Baumeister, Sabrina; Bitzer, Michael; Königsrainer, Alfred; Seufferlein, Thomas; Hoffmann, Rüdiger; Gatidis, Sergios; Nikolaou, Konstantin; Zips, Daniel; et al. (Frontiers in Oncology, 2023)
Introduction: Stereotactic body radiotherapy (SBRT) is an established ablative treatment for liver tumors with excellent local control rates. Magnetic resonance imaging guided radiotherapy (MRgRT) provides superior soft tissue contrast and facilitates a marker-less liver SBRT workflow. In the present study we report one of the largest cohorts of patients treated with online MRgRT of liver metastases with a focus on oncological outcome, patient reported outcome measures (PROMs), quality of life and toxicity. Material and methods: Patients treated for liver metastases with online MR-guided SBRT at a 1,5 T MR-Linac (Unity, Elekta, Crawley, UK) between March 2019 and December 2021 were included in this prospective study. For dose prescription and organs-at-risk constraints the UK SABR guidelines were followed. Oncological endpoints such as survival parameters (overall survival, progression-free survival) and local control as well as patient reported acceptance and quality of life data (EORTC QLQ-C30 questionnaire) were assessed. Toxicity was scored according to the Common Toxicity Criteria Version 5. Results: A total of 51 patients with 74 metastases were treated with a median of five fractions. The median applied BED GTV D98 was 84,1 Gy. Median follow-up was 15 months. Local control of the irradiated liver metastasis after 12 months was 89,6%, local control of the liver was 40,3%. Overall survival (OS) after 12 months was 85.1%. Progression free survival (PFS) after 12 months was 22,4%. Local control of the irradiated liver lesion was 100% after three years when a BED ≥100 Gy was reached. The number of treated lesions did not impact local control neither of the treated or of the hepatic control. Patient acceptance of online MRgSBRT was high. There were no acute grade ≥ 3 toxicities. Quality of life data showed no significant difference comparing baseline and follow-up data. Conclusion: Online MR guided radiotherapy is a noninvasive, well-tolerated and effective treatment for liver metastases. Further prospective trials with the goal to define patients who actually benefit most from an online adaptive workflow are currently ongoing.